Study On Proximal Composition of Illipe Nut (Shorea Stenoptera) - E.L.L. Lin; Rohaida Abdul Rasid @ Abdul Rashid; N.H.A. Daud (Faculty of Science and Natural Resources, 2020)
The study revolves around the Illipe nut (Shorea stenoptera); a nut that is abundantly available locally. The objective is to determine its proximate composition in its grinded form. After grinding, the collected samples are subjected to a series of proximal analysis where crude protein (6.46%), crude fat (51.73%), crude fiber (1.73%), moisture (5.64%), ash (3.10%) and aflatoxins (7.4ppb) content is determined. As it has significantly high amonts of fat, Illipe nuts could serve as an excellent phytogenic feed addictive in the diets of monogastric animals not only for better growth performance but also better-quality end products.